Foreign bodies in the ears in children: the experience of the Buenos Aires pediatric ORL clinic - Chinski, Alberto; Foltran, Francesca; Gregori, Dario; Passali, Desiderio; Bellussi, Luisa (The Turkish Journal of Pediatrics, 2011)
Even if foreign body (FB) insertion in the external auditory canal (EAC) is not an uncommon event, the literature based on large series is scarce. In the present study, ear FB cases observed at the Children's Hospital Gutierrez in Buenos Aires over five years of otorhinolaryngology (ORL) activity are presented, and the main findings are compared with data coming from other well-known published case series. Three hundred ninety-two injury cases were observed. Eighty percent of them occurred while the child was playing; in 328 cases (83.7%), adults were present. The retrieved FB included food items and objects usually available at home, such as pins, while fragments of toys were found in only 2 cases. These findings testify to the efficacy of regulations imposing manufacturing quality standards on toys; on the other hand, parents seem to be unaware of the risk imposed by FB insertion, since injuries usually happen under adult supervision while children are manipulating objects not adapted for their age.